The role of customer satisfaction in mediating the influence of price fairness and service quality on the loyalty of low cost carriers customers in Indonesia - Atmaja, Gede Karmeita Kusuma; Yasa, Ni Nyoman Kerti (International research journal of management, IT and social sciences, 2020)
The shift in transportation preference from using airplanes to land and water transportations has led to the problem of decreasing customer loyalty towards low-cost carriers (LCC) or airlines. To maintain customer loyalty, LCC must develop a strategy to make customers satisfied with their service and become less likely to change transportation preference. This research focuses on the role of customer satisfaction in mediating the influence of price fairness and service quality on the loyalty of LCC customers in Indonesia. This research is categorized as an associative quantitative study. The data consists of 175 samples, collected by distributing questionnaires which include open-ended and close-ended questions. The validity and reliability of these questions have also been verified. The analysis technique used is the structural equation modeling and the analysis tool utilized is SmartPLS 3.0. The research results revealed that the influence of price fairness on customer loyalty is positive and insignificant, service quality and customer satisfaction have a positive and significant influence on customer loyalty, price fairness and service quality have a positive and significant influence on customer satisfaction, price fairness fully mediates influence of customer satisfaction on customer loyalty, while customer satisfaction partially mediates influence of service quality on customer loyalty.